A compact time-to-amplitude converter for single-photon time-of-flight measurement. Issue 9 (21st May 2021) - Ma, Zhiqiang; Xu, Yue; Zhu, Sihui; Wu, Zhong
Abstract : This work proposes a compact time-to-amplitude converter (TAC) for single-photon time-of-flight (TOF) measurement. Based on the principle of current mirror integration, the regulated cascode output structure is used to improve the integration linearity. Fabricated in 180 nm standard CMOS technology, the test results show that the proposed TAC achieves an integral nonlinearity of less than 1.1 LSB, and a timing resolution of 78 ps in a full-scale range (FSR) of 20 ns. Moreover, the readout voltage only varies by 1% during 1 ms hold-off time. The simple circuit structure make TAC occupy a small area of 120 µm 2 and consume low dynamic power of 36.8 µW. The TOF measurement error is less than 5.2 cm, and the measurement precision is up to 1.61 cm at 150 cm. The presented TAC provides a compact implementation solution to realize high-density TOF sensors.